Toxicological evaluation of ethanolic extract of leaves from Doliocarpus dentatus in Swiss mice - Branquinho, Lidiane Schultz; Verdan, Maria Helena; dos Santos, Elisangela; Macorini, Luis Fernando Benitez; Maris, Rafael Souza; Kuraoka-Oliveira, Angela Midori; Bacha, Flávia Barbieri; Cardoso, Claudia Andrea Lima; Arena, Arielle Cristina [UNESP]; Silva-Filho, Saulo Euclides; Kassuya, Cândida Aparecida Leite (Taylor & Francis, 2021)
Doliocarpus dentatus (Dilleniaceae) has been used in folk medicine to treat inflammation and pain; however, studies evaluating its toxicity potential, as well as its effects on anxiety and depression, are scarce. This study investigated the toxicological profile of an ethanolic extract from leaves of D. dentatus (EEDd), and its effects on anxiety and depression models in mice. Male and female mice received either a single dose (500, 1000 or 2000 mg/kg) or repeated doses (75, 150 or 300 mg/kg) of EEDd by oral gavage. During the subacute toxicity assay, behavioral tests were performed on days 4, 14, 21 and 28. No evidence of toxicity was observed in the animals in both acute and subacute tests. However, males treated with the highest dose presented a reduction in the absolute weight of the kidney, an elevation in the AST levels, in addition to an alteration in the urea levels. The treatment did not affect other biochemical parameters, and did not induce any depressive-like behavior. EEDd exhibited low toxicity after single and repeated exposures. Since some analyzed parameters were compromised, further toxicity studies should be carried out.
Keywords: acute toxicity; anxiety; depressive-like behavior; Dilleniaceae; subacute toxicity